2020
DOI: 10.3389/fbioe.2020.00583
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical ex-vivo Testing of Anti-inflammatory Drugs in a Bovine Intervertebral Degenerative Disc Model

Abstract: Discogenic low back pain (LBP) is a main cause of disability and inflammation is presumed to be a major driver of symptomatic intervertebral disc degeneration (IDD). Anti-inflammatory agents are currently under investigation as they demonstrated to alleviate symptoms in patients having IDD. However, their underlying anti-inflammatory and regenerative activity is poorly explored. The present study sought to investigate the potential of Etanercept and Tofacitinib for maintaining disc homeostasis in a preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 85 publications
5
29
0
Order By: Relevance
“…In contrast to our experiments, these studies used lipopolysaccharides to stimulate inflammation in the respective cell cultures and might not be fully comparable. However, our workgroup recently validated the superior potential of TNF-α-induced inflammatory cell culture models to examine degenerative disc diseases Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 November 2020 doi:10.20944/preprints202011.0456.v1 [14]. Further, we showed that PPARγ pathway stimulation through losartan has protective effects on human NP cells for the first time.…”
Section: The Tissue Renin-angiotensin Systems -Angii As a Pro-inflammmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to our experiments, these studies used lipopolysaccharides to stimulate inflammation in the respective cell cultures and might not be fully comparable. However, our workgroup recently validated the superior potential of TNF-α-induced inflammatory cell culture models to examine degenerative disc diseases Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 17 November 2020 doi:10.20944/preprints202011.0456.v1 [14]. Further, we showed that PPARγ pathway stimulation through losartan has protective effects on human NP cells for the first time.…”
Section: The Tissue Renin-angiotensin Systems -Angii As a Pro-inflammmentioning
confidence: 81%
“…These strategies try to reduce the inflammatory microenvironment of the IVD in order to slow down the progressive degenerative cascade [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, ensuring a nutrient‐deprived ECM in whole disc culture may require more consideration and sophistication. A number of recent ex vivo disc organ studies have combined mechanical loading with low glucose culture medium to induce a catabolic niche and pro‐inflammatory cell response 11,15,23,35 . Another used short‐term glucose deprivation before refreshing the medium with a higher concentration of glucose 37 .…”
Section: Introductionmentioning
confidence: 99%
“…First, bovine caudal IVDs were used in this experiment, although several studies have noted that the mechanical performance and elastic modulus of bovine caudal IVDs and human lumbar IVDs are quite similar. [17][18][19][20][21] Second, the real-time range of motion of the IVD and the mechanical changes in different regions of the IVD were not measured during testing. Last, but not least, it would be ideal to perform a histological examination of the IVDs to observe the histological changes in the AF, endplate and NP after the biomechanical testing.…”
Section: Discussionmentioning
confidence: 99%